P351 Allogenic adipose-derived mesenchymal stem cells (darvadstrocel) in Japanese patients with complex perianal fistulas in Crohn's disease. (21st January 2022) - Watanabe, K; Mizushima, T; Okita, Y; Sugita, A; Nakaya, R; Shibata, M; Yamaguchi, T
Abstract: Background: Patients with complex Crohn's perianal fistulas were treated with allogenic mesenchymal stem cells (darvadstrocel) in pivotal studies, and in clinical practice in Europe since, 2018. However, it is unclear whether the same efficacy and safety could be expected across different ethnic groups. Moreover, it is known that perianal complications including perianal fistulas are more frequent in Asian patients with Crohn's disease (CD). Methods: Japanese adult patients with treatment-refractory complex perianal fistulas in CD were enrolled from, 9 sites in a phase, 3, open-label, single-arm, uncontrolled study. Patients could have, 2 internal and, 3 external openings at maximum, and their luminal disease was non-active or mildly active (CDAI ≤220) at baseline. A single dose (24mL, 120 million cells) of darvadstrocel was intralesionally injected, and results after, 24 and, 52 weeks were evaluated. Primary endpoint was combined remission (a remission rate evaluated clinically and by MRI) at Week 24. Results: 22 patients (mean age, 36.4 years, 63.6% male, mean duration of CD, 11.3 years) were enrolled. A half (11/22) had, 1 internal opening (IO) and, 2 external openings (EO) followed by, 1IO-1EO/2IO-2EO/2IO-3EO (3 each, 9/22) and, 1IO-3EO (2/22)., 59.1% and, 68.2% achieved combined remission at Week, 24 (primary endpoint) and Week, 52, respectively. Up to Week, 52, 90.9% (20/22) experienced adverse events (AE), and, 81.8% (18/22) were mild or moderate in intensity. Proctalgia (6/22), nasopharyngitis (5/22), and anal fistula (4/22) were most frequently reported. There was no death or AE-related study discontinuation. Conclusion: 52 weeks after administrating darvadstrocel in Japanese patients with complex perianal fistulas in CD, fistula closure was confirmed in, 68% (15/22) and partial closure in, 90.0% (20/22). These findings are consistent with the pivotal study ADMIRE-CD, and real-world case-series reported from Europe. Furthermore, no new safety concerns were identified.